Rac‐GTPase promotes fibrotic TGF‐β1 signaling and chronic kidney disease via EGFR, p53, and Hippo/YAP/TAZ pathways. Issue 9 (16th May 2019) - Patel, Samik; Tang, Jiaqi; Overstreet, Jessica M.; Anorga, Sandybell; Lian, Fei; Arnouk, Alex; Goldschmeding, Roel; Higgins, Paul J.; Samarakoon, Rohan
ABSTRACT: Rac‐GTPases are major regulators of cytoskeletal remodeling and their deregulation contributes to numerous pathologies. Whether or how Rac promotes tubulointerstitial fibrosis and chronic kidney disease (CKD) is currently unknown. We showed that the major profibrotic cytokine, TGF‐β1 promoted rapid Rac1‐GTP loading in human kidney 2 (HK‐2) human renal epithelial cells. A Rac‐specific chemical inhibitor, EHT 1864, blocked TGF‐β1‐induced fibrotic reprogramming in kidney epithelial cells and fibroblasts. Stable Rac1 depletion in HK‐2 cells, moreover, eliminated TGF‐β1‐mediated non‐SMAD pathway activation [ e.g ., Src, epidermal growth factor receptor (EGFR), p53] and subsequent plasminogen activator inhibitor‐1 (PAI‐1), connective tissue growth factor, fibronectin, and p21 induction. Rac1 and p22 phox knockdown abrogated free radical generation by TGF‐β1 in HK‐2 cells, consistent with the role of Rac1 in NAPD(H). TGF‐β1‐induced renal epithelial cytostasis was also completely bypassed by Rac1, p22 phox, p47 phox, and PAI‐1 silencing. Rac1b isoform expression was robustly induced in the fibrotic kidneys of mice and humans. Intraperitoneal administration of EHT 1864 in mice dramatically attenuated ureteral unilateral obstruction‐driven EGFR, p53, Rac1b, yes‐associated protein/transcriptional coactivator with PDZ‐binding motif activation/expression, dedifferentiation, cell cycle arrest, and renal fibrogenesis evident in vehicle‐treated obstructed kidneys. Thus, the Rac1‐directed redox response is critical for TGF‐β1‐driven epithelial dysfunction orchestrated, in part, via PAI‐1 up‐regulation. Rac pathway inhibition suppressed renal oxidative stress and maladaptive repair, identifying Rac as a novel therapeutic target against progressive CKD.—Patel, S., Tang, J., Overstreet, J. M., Anorga, S., Lian, F., Arnouk, A., Goldschmeding, R., Higgins, P. J., Samarakoon, R. Rac‐GTPase promotes fibrotic TGF‐β1 signaling and chronic kidney disease via EGFR, p53, and Hippo/YAP/TAZ pathways. FASEB J. 33, 9797–9810 (2019). www.fasebj.org